1988
DOI: 10.3109/01902148809115123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Corticosteroids on Lung Volume-Pressure Curves in Bleomycin-Induced Lung Injury in the Rat

Abstract: In this study we investigated changes in volume-pressure curves at various stages after bleomycin induced lung injury (6 h, and 3, 7, and 28 days) and tested the ability of steroids to influence these changes. The most significant decreases in volume-pressure curves were observed at 3 days post bleomycin, a time point that correlates to the peak period of inflammation. Steroids as drugs of high antiinflammatory potency were used in order to modulate the inflammatory response and possibly the volume-pressure cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In animal models of endotoxic shock, prophylactic treatment with dexamethasone attenuates the production of inflammatory cytokines including TNF-α and IL-1β, and prevents shock and mortality [ 24 ]. Previous studies using prolonged administration of corticosteroids, such as methylprednisolone or dexamethasone, initiated before or simultaneously with bleomycin reduced pulmonary inflammation, lung injury, and collagen deposition in this model [ 25 27 ].…”
Section: Discussionmentioning
confidence: 94%
“…In animal models of endotoxic shock, prophylactic treatment with dexamethasone attenuates the production of inflammatory cytokines including TNF-α and IL-1β, and prevents shock and mortality [ 24 ]. Previous studies using prolonged administration of corticosteroids, such as methylprednisolone or dexamethasone, initiated before or simultaneously with bleomycin reduced pulmonary inflammation, lung injury, and collagen deposition in this model [ 25 27 ].…”
Section: Discussionmentioning
confidence: 94%
“…[21][22][23] Although an important finding, its clinical relevance is questionable as anti-inflammatory treatment is always given after lung damage has occurred. In our study the corticosteroid concentration used was much lower than in previous studies, 21-23 treatment was initiated after bleomycin induced lung injury, and it was only administered for a short time.…”
Section: Discussionmentioning
confidence: 99%
“…19 20 Previous studies using prolonged administration of corticosteroids such as methylprednisolone or dexamethasone initiated before or simultaneously with bleomycin reduced pulmonary inflammation, lung injury, and collagen deposition in this model. [21][22][23] However, as anti-inflammatory treatment usually starts after lung injury has occurred, the clinical relevance of starting treatment in animals before or at the time of injury is questionable.…”
mentioning
confidence: 99%
“…The initial studies in animal models (mostly conducted in the rat) showed that glucocorticoids clearly reduced bleomycin-induced pulmonary fibrosis by reducing collagen synthesis and deposition (Phan et al 1981;Sterling et al 1982). Later studies suggested that decreased inflammatory cell infiltration (Grunze et al 1988), decreased parenchymal cell proliferation (Dik et al 2003b), and increased parenchymal inflammatory cell apoptosis ) might also contribute to the antifibrotic effects of glucocorticoids. However, these findings have not been universally confirmed.…”
Section: Figmentioning
confidence: 97%